Lateral root initiation in Arabidopsis thaliana: a force awakens - Vermeer, Joop E. M. (F1000Prime Rep, 2015)
Osmotically driven turgor pressure of plant cells can be higher than that of a car tire. It puts tremendous forces onto cell walls and drives cell growth and changes in cell shape. This has given rise to unique mechanisms to control organ formation compared to metazoans. The fascinating interplay between forces and local cellular reorganization is still poorly understood. Growth of lateral roots is a prominent example of a developmental process in which mechanical forces between neighboring cells are generated and must be dealt with. Lateral roots initiate from a single cell layer that resides deep within the primary root. On their way out, lateral roots grow through the overlying endodermal, cortical, and epidermal cell layers. It was recently demonstrated that endodermal cells actively accommodate lateral root formation. Interfering genetically with these accommodating responses in the endodermis completely blocks cell proliferation in the pericycle. The lateral root system provides a unique opportunity to elucidate the molecular and cellular mechanisms whereby mechanical forces and intercellular communication regulate spatial accommodation during plant development.